Analisis Pengaruh Pembiyaan, Pembinaan, Promosi Terhadap Kemampuan Usaha Mikro dan Peningkatan Kesejahteraaan Usaha Mikro pada Anggota Koperasi Syariah - Indah Apriyani Nasution (CV. Syntax Corporation Indonesia, 2022)
The presence of financial services cooperatives is a form of people's economic movement. Cooperatives, including savings and loan cooperatives, are a form of policy for overcoming social welfare problems in the context of empowering the community's economy. the purpose of the cooperative is the welfare of its members and the programs provided by the cooperative to create new jobs for the community and the members of the cooperative. The type of research used in this research is quantitative research. This research in this research is all members of sharia cooperatives who work at the Kaum Ibu Al-Ikhlas Sharia Cooperative, Medan City, which are registered in the 2021 BPS, with a total of 152 members. Based on the results of the hypothesis analysis, it was obtained that P Values (0.00222) <0.05 and t statistics (3.07501) > 1.96, it was concluded that Financing had a significant effect on Micro Enterprise Capability. Based on the results of the analysis obtained P Values (0.00111) <0.05 and t statistics (3.28092) > 1.96, it is concluded that Coaching Has a Significant Influence on the Capabilities of Micro Enterprises.